Optimal Energy Management for Renewable Energy Microgrids - Carlos Bordons; Félix García Torres; Luis Valverde (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This paper deals with some issues related to optimal operation of microgrids, which are a group of loads, generators and energy storage systems that can be managed isolated or connected to the main grid, in a coordinated way in order to reliably supply electricity. The control problems and solution are addressed both for optimal dispatch and for the integration of the microgrid in the electricity market. Development of Model Predictive Controllers are presented for case studies that include several renewable sources (photovoltaic and wind) as well as hybrid storage using hydrogen. Some experimental results for a demonstration microgrid are presented, as well as simulations of scheduling in the electricity market. The results indicate that development of the appropriate controllers will allow a competitive participation of renewable energy in the new model of the electrical system.